Movimentos sociais e propriedade: a efetividade da função social da propriedade rural - Castro, Guthemberg Cardoso Agra de (2010)
The present dissertation work has as principal finality to contribute with the law operators, as well as to give assistance to social movements, who dial with the agrarian issue in our country. The social function of property has no other objective than to extent the economic property concept, confronting it as a richness that destine itself to the production of properties that satisfy the social needs, it means, the right to private properties over others properties will be inherently connected to social function. This limitation of law property can be summarized with the accomplishment of common welfare, also understood as community welfare. It means that, the State, having as his principal objective the attainment of common welfare, will never should sacrifice any of the fundamental human rights. The social function of property represents the recognition of whole holder domain, that for being member of a community, has rights and obligations in relation to others members of this same community; in a manner that, if he can come to be a holder domain, has the obligation to fulfill with the right of others people, that consist in do not realize any act that may prevent or cause trouble to the community welfare. In agrarian law, specifically to the rural property, it fells to be the right of property to capacity that a person has to have it as its own, with the correlate duty to use it as well as require the community welfare. There is, in the other hand, a lack of a specific legislation, that can not, this institute, to be applied, in your whole, in the everyday lives of the Brazilians; as we will see during this dissertation, observing that the Judiciary and our civilian codes almost always safeguard with much vehemence the absolute and inviolable property right